The Effect of Workload and Occupational Health Safety on the Performance of Production Employees at PT. Indovickers Furnitama - Rafif Muhammad Wijdan; Irbayuni, Sulastri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to explain the effect of workload and occupational safety and health on the performance of production employees at PT. Indovickers Furnitama. The population in this study is employees of the production department of PT. Indovickers Furnitama, 40 responders made up the study's sample, however. Every test conducted using the SmartPLS Application demonstrates that all test results are higher than those necessary to be deemed genuine. In this work, PLS analysis, descriptive statistics, and a quantitative research design were employed for data analysis. The findings demonstrated that the workload had a noteworthy adverse impact and could not be used to boost PT staff' performance. Indestructibles Furnitama. When it comes to enhancing employee performance in production workers, occupational safety and health has a major beneficial impact.